OPTIMALISASI PERENCANAAN KAPASITAS PRODUKSI DENGAN METODE THEORY OF CONSTRAINTS DAN ROUGH CUT CAPACITY PLANNING - Oktaviana Claudia Situmorang; Ririn Regiana Dwi Satya; Aditya Herliawan (Fakultas Teknik, Universitas Singaperbangsa Karawang, 2023)
PT. MTI has a problem that often occurs in planning its production capacity, where there are often delays in the delivery of ordered products. One of the causes is also the inhibition of the production process at one of the workstations, resulting in the flow of the production process. Theory Of Constraints (TOC) is an improvement method that helps in making decisions in managing resources. The TOC method is also very useful for optimizing production capacity by analyzing and minimizing time constraints that support production. In addition, the Rough Cut Capacity Planning (RCCP) method is a method for calculating capacity requirements and comparing them with the available capacity. The data used in this study are product demand data, product processing time, product structure, and working hours. From the results of data processing with the TOC approach, it was found that the workstation experiencing obstacles was the welding workstation and the amount of buffering at the workstation was 5.22 hours before the workstation and 4.97 hours after the obstacle station. And the results of data processing with RCCP and LINDO software get the optimal production capacity produced by PT. MTI is 181 units per month with the distribution of 101 units for Pallet 1A, and 80 units for Pallet 3A, and based on the largest MPS comparison, it is stated that the company's capacity is not sufficient to meet the largest demand for MPS in November. So the company needs to increase the working hours overtime or by adding several units of machines to the workstation constrained by the welding station.